TINJAUAN PENYUSUNAN BIAYA OPERASIONAL ATAS AKTIVITAS EKSPOR KARET PADA PT. PANCA SAMUDERA SIMPATI - Dika Perkasa; Teofilus Sabamtua Tambunan; Maulan Irwadi (Jurnal Ilmiah Ekonomi Global Masa Kini)
Budget analysis of operational costs is the one method for company to do some effective cost control on its operation, especially in companies that do export ectivity. PT. Pancasamudera Simpati is one of the most Crumb Rubber Company in Palembang City and they do export the rubber to abroad, such us : U.S.A, China, Jepan, etc. Export activity for breakbulk shipment that carried on PT. Newship Nusabersama as shipping company also need to monior and it is important to analysis of the operational budget on activities that have been performed. Thus company know the actual costs of the budget and do the planning for the next operation so that coporate objectives can be achived. In its export activity, wrongly loading the cargo onto the barges, extra cost of barges rental and huge overtime cost its a few problem that can increase of the budget. This research method used is descriptive qualitative and quantitative methods. The result of analysis of the budget for operational costs PT. Pancasamudera Simpati, can be concluded that the cost deviation is not profitable deviation of deviation favorable. Then, the preparation of the budget is good planning as per cost standar from last operation and improvement efforts on activities implemented.Keyword : Budget, Operational Cost, Export, Variance